ANALISIS PENGGUNAAN TEKNOLOGI DAN PERALATAN RUMAH TANGGA DI ERA MODERN PADA MASYARAKAT BADUY LUAR - Neli Nurmala; Sapriya; Encep Supriatna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This article discusses the analysis of the technological and living equipment of the Baduy Luar community, an indigenous community in Banten Province, Indonesia. This research aims to identify and understand how traditional technology, such as agricultural tools, food processing systems, and daily equipment, contributes to the sustainability of the lives of the Outer Baduy community. This research uses a qualitative approach with ethnographic methods to understand in depth the technological systems and living equipment of the Outer Baduy community. This method was chosen because it is able to explore cultural meanings and social practices in the context of everyday life. The research location was carried out in the Kanekes area, Lebak Regency, Banten, with a focus on villages inhabited by the Outer Baduy community. Data was collected through direct observation, in-depth interviews and documentation studies. The research results show that the Outer Baduy people rely on simple, environmentally friendly technology, which not only meets their daily needs but also preserves their cultural values. Apart from that, the adaptation of modern technology is hampered by local wisdom and deeply held social norms. These findings provide an important perspective for developing policies that respect local wisdom in facing modernization.